Identification of two HLA-A*0201 immunogenic epitopes of lactate dehydrogenase C (LDHC): potential novel targets for cancer immunotherapy - Remy Thomas (702843) (2020)
Lactate dehydrogenase C (LDHC) is an archetypical cancer testis antigen with limited expression in adult tissues and re-expression in tumors. This restricted expression pattern together with the important role of LDHC in cancer metabolism renders LDHC a potential target for immunotherapy. This study is the first to investigate the immunogenicity of LDHC using T cells from healthy individuals. LDHC-specific T cell responses were induced by in vitro stimulation with synthetic peptides, or by priming with autologous peptide-pulsed dendritic cells. We evaluated T cell activation by IFN-γ ELISpot and determined cytolytic activity of HLA-A*0201-restricted T cells in breast cancer cell co-cultures. In vitro T cell stimulation induced IFN-γ secretion in response to numerous LDHC-derived peptides. Analysis of HLA-A*0201 responses revealed a significant T cell activation after stimulation with peptide pools 2 (PP2) and 8 (PP8). The PP2- and PP8-specific T cells displayed cytolytic activity against breast cancer cells with endogenous LDHC expression within a HLA-A*0201 context. We identified peptides LDHC41−55 and LDHC288−303 from PP2 and PP8 to elicit a functional cellular immune response. More specifically, we found an increase in IFN-γ secretion by CD8 + T cells and cancer-cell-killing of HLA-A*0201/LDHC positive breast cancer cells by LDHC41−55- and LDHC288−303-induced T cells, albeit with a possible antigen recognition threshold. The majority of induced T cells displayed an effector memory phenotype. To conclude, our findings support the rationale to assess LDHC as a targetable cancer testis antigen for immunotherapy, and in particular the HLA-A*0201 restricted LDHC41–55 and LDHC288–303 peptides within LDHC. Other Information Published in: Cancer Immunology, Immunotherapy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00262-020-02480-4